Informal learning and identity formation in online social networks - Greenhow, Christine; Robelia, Beth (Learning, media and technology, 2009)
All students today are increasingly expected to develop technological fluency, digital citizenship, and other twenty-first century competencies despite wide variability in the quality of learning opportunities schools provide. Social network sites (SNSs) available via the internet may provide promising contexts for learning to supplement school-based experiences. This qualitative study examines how high school students from low-income families in the USA use the SNS, MySpace, for identity formation and informal learning. The analysis revealed that SNSs used outside of school allowed students to formulate and explore various dimensions of their identity and demonstrate twenty-first century skills; however, students did not perceive a connection between their online activities and learning in classrooms. We discuss how learning with such technologies might be incorporated into the students' overall learning ecology to reduce educational inequities and how current institutionalized approaches might shift to accommodate such change.